Sejarah Revolusi Sosial Di Langkat Tahun 1946 - Agung meiranda (Program Studi Pendidikan Sejarah - Universitas Samudra, 2021)
This research is intended to determine the triggering factors for the Social Revolution in Langkat in 1946, how the tragedy of the Social Revolution in Langkat took place and what impact happened to the social structure of the Langkat community after the incident. The research procedure used is a critical historical research methodology which consists of several aspects, namely Heuristic, Source Criticism, Interpretation and Historiography. This research uses literary sources plus interviews. The results of this paper prove that there was an interrelation between the Dutch government and the aristocratic family of the Langkat Sultanate which led to a polemic due to the fading of people's trust in local government. Then social movements emerged from the lower society. This movement on behalf of the United Struggle which was masterminded by a group of parties acting on behalf of the People's Struggle moved to eliminate the local political elite in East Sumatra. This incident also led to the death of many families of the Sultanate of Langkat and one of our national hero figures to die in it, namely Tengku Amir Hamzah.